Rural infrastucture, the settlement system, and development of the regional economy in Southern India - Wanmali, Sudhir (International Food Policy Research Institute, 1992)
North Arcot, a rural district of Tamil Nadu, India, has been the site of extensive research on whether economic growth induced by the introduction of the green revolution has widened inequities between the well-to-do and the poor. Data indicate that not only landless laborers and small-scale farmers in this area have benefited, but also small businesses and services. Using that and additional data from North Arcot, Rural Infrastructure, the Settlement System, and Development of the Regional Economy in Southern India, Research Report 91, by Sudhir Wanmali, approaches the question from another direction: How important is the provision of infrastructure--hard and soft--to economic growth in a rural region? Policymakers usually consider the effects of rural infrastructure on agriculture in terms of hard infrastructure--roads, electricity, irrigation. But other types of infrastructure are just as important. Institutional infrastructure such as government agencies is needed to collect and analyze local data before agricultural development is planned. Soft infrastructure including transport, finance, input distribution, and marketing services is also essential. This study finds that available and accessible services help improve total production and the productivity of agriculture and help strengthen linkages between agricultural and nonagricultural sectors.